2022
DOI: 10.1007/s10654-022-00902-4
|View full text |Cite
|
Sign up to set email alerts
|

The long-term relation between physical activity and executive function in the Rotterdam Study

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 78 publications
1
2
0
Order By: Relevance
“…This evidence contributes to consolidating the positive association between PA and EFs in university students. In this sense, the positive links between PA and EFs observed in this study are consistent with extensive sections of the literature [64][65][66][67][68]. In this context, a systematic review reported that PA can be a way to improve cognitive outcomes and language skills in adolescents and young adults [69].…”
Section: Discussionsupporting
confidence: 90%
“…This evidence contributes to consolidating the positive association between PA and EFs in university students. In this sense, the positive links between PA and EFs observed in this study are consistent with extensive sections of the literature [64][65][66][67][68]. In this context, a systematic review reported that PA can be a way to improve cognitive outcomes and language skills in adolescents and young adults [69].…”
Section: Discussionsupporting
confidence: 90%
“…This involves spontaneous recovery and care processes that enable defining the actions to be carried out based on the place and situation. High levels of physical activity correlated directly with the proper functioning of EF, suggesting a potential palliative measure (Galle et al, 2022). The study of Galle et al (2023) showed that those who increased their physical activity by more than 30% displayed improvements in gait speed, aerobic capacity, EF, and global cognition compared to those who did not.…”
Section: Benefits In Cognitive Functionsmentioning
confidence: 99%
“…Research has unequivocally demonstrated wide-ranging, and well-documented health benefits of regular PA on physical, cognitive and mental health even at an older age (2)(3)(4)(5)(6). Based on evidence, the WHO recommends that individuals aged 65 and above should engage in at least 150 min moderate-intensity aerobic PA, or at least 75 min of vigorous-intensity aerobic PA weekly, supplemented with musclestrengthening activities at least 2 days per week and balance or multicomponent exercises (7).…”
Section: Introductionmentioning
confidence: 99%